FRUIT GROWING AND VITICULTURE FROM THE STANDPOINT OF FUTURE DEVELOPMENT OF SERBIA - Maletić, Radojka; Ceranić, Slobodan (Economics of Agriculture, 2010)
The aim of the study was to analyze trends of intensivity of fruit growing and viticulture production in Serbia considered to be of major importance in agricultural production. Yield and production data in fruit and viticulture growing were analyzed for the period 1970-2005. Positive agri-policy measures and systemic solutions at the Republic level may contribute to the spread of biodiversity of the productions (including processing capacities). Thus Serbia would rank high and may be expected to play the leading role in the production, processing and export of fruit and grapes both in the Balkans and Europe.